Estenose da artéria do enxerto renal : prevalência e fatores associados em uma unidade de transplante renal - Nasserala, Jarinne Camilo Landim (2016)
Introduction: The transplant renal artery stenosis (TRAS) is the most common vascular complication post-kidney transplant (Tx) that can lead to resistant hypertension, impaired renal function and even loss of the graft. Objectives: To investigate the prevalence and factors associated with TRAS. Methods: A retrospective case-control study was carried out in a population of Tx recipients from January 2008 to March 2014 in a renal Tx reference center in northeastern Brazil. Demographic and clinical characteristics of the recipient and donor, data related to the surgery, laboratory data and number of antihypertensive drugs were assessed as factors associated with TRAS. Statistical analysis was performed using SPSS 17.0. Results: A total of 494 of 529 recipients were assessed, of which 24 had TRAS. The prevalence of TRAS was 4.8% (24 patients), of which 23 had a deceased donor. Twelve patients (50%) were males, mean age of 46.7 ± 13.5 years (range 17-78 years). Mean time of diagnosis was 89.9 days post-Tx. The risk factors associated with TRAS were number of antihypertensive drugs ≥ 2 (OR: 17.0; CI: 4.1 to 70.4, p = 0.001) and grafting with two or more arteries (OR 8.9, CI: 1.4 -56.6, p = 0.021). There was a significant reduction in mean SBP (147.1 ± 23.7 to 127.8 ± 15.2 mmHg, p = 0.001) and DBP (86.6 ± 13.0 to 77.6 ± 9.4 mmHg, p = 0.001) after TRAS repair, as well as in serum creatinine (2.8 ± 2.4 to 1.9 ± 1.8 mg / dL, p = 0.04). Conclusion: The prevalence of TRAS maintained the pattern described in the literature and grafts with two or more arteries are associated with TRAS, as well as patients that use a higher number of antihypertensive drugs. TRAS repair was associated with improved blood pressure control and renal function.